The Optimization of Canola Crop Production through Wheat Residue Management within a Western Canadian Context—A Case Study of Saint-Front, Saskatchewan - Xiaying Xin (Sustainability, 2021)
In this study, the processes of wheat residue degradation in combination with various tillage treatments were explored to determine the ideal management prescription for maximizing canola crop production. A field experiment within a western Canadian context (near Saint-Front, Saskatchewan), consisting of a 2 × 3 factorial design, was conducted to determine the fate of crop residue under different harvest and treatment scenarios. ATR-Fourier transform infrared (FTIR) spectroscopy, FTIR spectromicroscopy, and synchrotron-based X-ray fluorescence imaging (SR-XFI) were used to explore wheat residue degradation mechanisms. The results indicated maximum canola yields and residue degradation occurred in combination with a combine outfitted with an aftermarket chopper and post-harvest treatment by harrow. Crop residue degradation was attributed to cellulose/linen hydrolysis and supramolecular structure changes from high crystalline to amorphous cellulose. Multi-element loss usually accompanied crop residue degradation. An important aspect of this study is the adoption of field-scale analysis to accurately portray real-world sustainable management techniques within a western Canadian context. The findings provided an optimal combination of crop residue treatment and tillage treatment to increase canola production, which had the potential ability to be applied in other countries. It is also an initial attempt to develop a technical composite of FTIR spectromicroscopy and SR-XFI for examining the mechanism of residue decomposition.